STRENGTHENING DIGITAL LITERACY TOWARDS INDONESIAN DIGITAL SOVEREIGNTY - Benny Ranti; K.P. Suharyono S. Hadiningrat; Yosi Widhayanti (Yayasan Inspirasi Merah Putih Indonesia, 2024)
Digital Literacy is closely related to the use of digital technology and user readiness in utilizing digital technology. Mastery of technological and information advances makes humans think more creatively and innovatively. The ability of users in digital literacy includes the ability to create, use, create, utilize and evaluate the appropriate use of digital technology in everyday life. Digital sovereignty is the right and ability of a party to manage and control its own digital data both on content and information circulation. Indonesia's digital literacy index in 2022 shows a value of 3.54 or falls into the “medium” category, which means that there are still many improvements that can be made so that the literacy index can improve. Digital sovereignty is the ability of a party to control its own digital data, including control over the digital environment around it, including access to personal data. Activities to strengthen digital literacy to support Indonesia's digital sovereignty, including Indonesia being directed to shift from digital consumers to digital producers, encouraging the development of hardware and software in Indonesia, creating a digital development ecosystem, making a digital literacy blueprint, making policies or rules related to personal data protection and continuous education to the community.